2021
DOI: 10.1021/acs.langmuir.1c01136
|View full text |Cite
|
Sign up to set email alerts
|

Using Patterned Self-Assembled Monolayers to Tune Graphene–Substrate Interactions

Abstract: Graphene has unique mechanical, electronic, and optical properties that make it of interest for an array of applications. These properties can be modulated by controlling the architecture of graphene and its interactions with surfaces. Self-assembled monolayers (SAMs) can tailor graphene–surface interactions; however, spatially controlling these interactions remains a challenge. Here, we blend colloidal lithography with varying SAM chemistries to create patterned architectures that modify the properties of gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Depositing Graphene. The deposition of graphene on our substrates employed a method developed in-lab, 46 which was initially adapted from Song et al 47 Briefly, CVD-grown graphene on Cu was purchased (LG), and polystyrene (PS− MW 13 000, Sigma-Aldrich) at 31.5 mg/mL in toluene was spin-coated onto the surface at 300 rpm for 2 min as a selfreleasing layer. It was heated to 85 °C for 5 min to remove the solvent.…”
Section: Fabrication Ofmentioning
confidence: 99%
“…Depositing Graphene. The deposition of graphene on our substrates employed a method developed in-lab, 46 which was initially adapted from Song et al 47 Briefly, CVD-grown graphene on Cu was purchased (LG), and polystyrene (PS− MW 13 000, Sigma-Aldrich) at 31.5 mg/mL in toluene was spin-coated onto the surface at 300 rpm for 2 min as a selfreleasing layer. It was heated to 85 °C for 5 min to remove the solvent.…”
Section: Fabrication Ofmentioning
confidence: 99%
“…Our studies point to the ability to direct molecular migration experimentally as a means of tuning the physicochemical properties of 2D materials. We have previously shown that spatially controlled functionalization of graphene with azides can yield localized scattering of the graphene plasmon, and thus by depositing graphene on patterned substrates with controlled localized curvature, one can envision tracking migration to locations of high localized curvature using spatially resolved vibrational spectroscopies, , near-field scattering, or high-resolution optical fluorescence measurements …”
Section: Resultsmentioning
confidence: 99%
“…This can be realized by bonding a terminal N group across the CC bond network of graphene, forming an aziridine ring, with individual molecule–graphene bonds breaking and reforming as the molecule moves. This class of functionalization has been reported to locally open a band gap in graphene, , and therefore it provides a way to tailor nanomaterials for optoelectronic purposes . Migration of a functionalized center on graphene provides a way to spatially control the local frontier energy levels as well as the carrier (electron/hole) concentrations and defect states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A discussion on surface passivation of graphene with PDs has been reported elsewhere . To reach at least about 90% surface coverage by a monolayer of PDs and to avoid the formation of dimers or trimers, surfaces of the sensors were rinsed with a compatible solvent. , Table shows the specific information on the PDs and corresponding solvents used in this work.…”
Section: Materials and Experimental Designmentioning
confidence: 99%